2014
DOI: 10.1007/s10295-014-1444-1
|View full text |Cite
|
Sign up to set email alerts
|

Operation performance and microbial community dynamics of phosphorus removal sludge with different electron acceptors

Abstract: Operation performances of phosphorus removal sludge with different electron acceptors in three parallel SBRs were firstly compared in the present study, and the effect of post-aeration on denitrifying phosphorus removal was also studied. Moreover, community dynamics of different phosphorus removal sludge was systematically investigated with high-throughput sequencing for the first time. TP removal rates for nitrate-, nitrite-, and oxygen-based phosphorus removal sludge were 84.8, 78.5, and 87.4 %, with an aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The phylum Proteobacteria is a highly diverse phenotypic and phylogenetic lineage (Kersters et al, 2006) (Hahn, 2003). The sand filter pond had abundant species belonging to the genus Dechloromonas (accounting for 11.50% ± 0.02), which was absent in the other samples, and several studies have identified members of this genus as denitrifying polyphosphate-accumulating organisms (DPAOs) Dai, Wu, et al, 2017;Lv et al, 2014). Moreover, members of the genus Synechococcus have been reported to remove nutrients (total nitrogen and total phosphorus) from wastewater (Deng, Gao, & Sun, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The phylum Proteobacteria is a highly diverse phenotypic and phylogenetic lineage (Kersters et al, 2006) (Hahn, 2003). The sand filter pond had abundant species belonging to the genus Dechloromonas (accounting for 11.50% ± 0.02), which was absent in the other samples, and several studies have identified members of this genus as denitrifying polyphosphate-accumulating organisms (DPAOs) Dai, Wu, et al, 2017;Lv et al, 2014). Moreover, members of the genus Synechococcus have been reported to remove nutrients (total nitrogen and total phosphorus) from wastewater (Deng, Gao, & Sun, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…DPAO can be readily selected in a sequencing batch reactor (SBR) operated in anaerobic/anoxic mode by dosing nitrate or nitrite during the anoxic phase. 15,16 Tsuneda et al 17 used anaerobic-oxic-anoxic (AOA) operation mode to select DPAO by dosing supplemental carbon at the beginning of the oxic phase in order to encourage oxygen use by heterotrophic bacteria so as to provide competition for this electron acceptor to polyphosphate accumulating organisms (PAO); they then measured anoxic phosphate uptake rate and aerobic phosphate uptake rate. For comparison, they also measured the ratio of anoxic phosphate uptake rate to aerobic phosphate uptake rate of biomass taken directly from a wastewater treatment plant applying an anaerobic-anoxicoxic (AAO) process, and from a lab-scale SBR operating in anaerobic-oxic mode.…”
Section: Introductionmentioning
confidence: 99%